Innovative Didactic Strategies to Stimulate Meaningful Learning of Geographic Space in Secondary School Students (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2023)
The activity of human groups can have serious consequences in the geographical space. The objective of this article was to analyze the innovative didactic strategies that stimulate the meaningful learning of geographic space in secondary school students. The methodology was of a descriptive documentary type with a bibliographic design, through searches in libraries, university repositories and databases, among others. The results indicate that in order to prevent and reduce environmental impacts and biodiversity, innovative didactic strategies are required in teaching that allow students to assimilate and understand the functioning of geographic space.
Keywords: Innovative teaching strategies; meaningful learning; geographic space; secondary education; sustainable practices